Komponisten im Gulag der Stalinzeit: Композиторы в ГУЛАГе в годы правления Сталина - Klause, Inna; Waczkat, Andreas; Weiss, Stefan (Georg Olms Verlag, 2024)
During the Stalin era, more than 18 million people were imprisoned in the Gulag, the system of forced labor camps in the Soviet Union, among them numerous musicians. Of the many music-related professions that were represented in the Gulag at the time, this volume focuses on composers. It documents the facts on this subject that are currently known and places the fates of the people concerned in a wider context by asking about the background to the imprisonments, placing them in the context of other repressions against musicians in the Soviet Union and taking a sideways look at other arts in the same place. With contributions byInna Barsova | Friedrich Geiger | Igor Golomshtok | Galina Ivanova | Inna Klause | Marina Lobanova | Urve Lippus | Wolfgang Mende | Victoria Mironova | Jascha Nemtsov | Dorothea Redepenning | Vitaly Shentalinsky | Oleg Timofeyev | Semyon Vilensky | Igor Vorobyov | Andreas Waczkat | Felicitas Fischer von Weikersthal | Stefan Weiss | Vsevolod Zaderatsky